2015
DOI: 10.1186/s13007-015-0060-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of MRI and X-ray CT technologies for 3D imaging of root systems in soil: potential and challenges for root trait quantification

Abstract: BackgroundRoots are vital to plants for soil exploration and uptake of water and nutrients. Root performance is critical for growth and yield of plants, in particular when resources are limited. Since roots develop in strong interaction with the soil matrix, tools are required that can visualize and quantify root growth in opaque soil at best in 3D. Two modalities that are suited for such investigations are X-ray Computed Tomography (CT) and Magnetic Resonance Imaging (MRI). Due to the different physical princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(202 citation statements)
references
References 53 publications
2
182
0
1
Order By: Relevance
“…1B). As MRI, root analysis with x-ray CT also acquires, with current root segmentation procedures, similar fractions of roots compared to WinRHIZO (Flavel et al, 2012;Metzner et al, 2015). Koebernick et al (2014) reported a detection of near 100% for roots of Vicia faba regarding only roots .500 mm.…”
Section: Discussionmentioning
confidence: 99%
“…1B). As MRI, root analysis with x-ray CT also acquires, with current root segmentation procedures, similar fractions of roots compared to WinRHIZO (Flavel et al, 2012;Metzner et al, 2015). Koebernick et al (2014) reported a detection of near 100% for roots of Vicia faba regarding only roots .500 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Samples are certainly more easily prepared for MRI than X‐ray CT, in particular for those studies which require metal‐based staining for soft tissue imaging (Metscher, 2009a, 2013). Nevertheless, magnetic resonance scanning systems are limited in resolution (Metscher, 2013; Metzner et al., 2015) and often have prohibitive costs of operation (Ziegler et al., 2011). Furthermore, air spaces routinely found in biological samples can cause artifacts in MRI (Jasanoff & Sun, 2002; Wecker, Hörnschemeyer, & Hoehn, 2002; Ziegler et al., 2011).…”
Section: Techniques For Tomographic Reconstructionsmentioning
confidence: 99%
“…Several root screening approaches involve the application of three-dimensional (3D) imaging techniques. The most promising technique for noninvasive 3D imaging in soil is X-ray computed tomography (CT) and magnetic resonance imaging (MRI) (Metzner et al 2015). There are also other applicable approaches that include selective plane illumination microscopy (SPIM) and optical projection omography (OPT) that are adapted for plants grown in transparent media (Downie et al 2012).…”
Section: Root Phenotyping Of Cereal Plantsmentioning
confidence: 99%